â€œANALISIS PENGARUH KUALITAS PRODUK DAN BRAND IMAGES TERHADAP BEHAVIOURAL INTENTION PADA KONSUMEN ANTIMO DI KOTA SEMARANGâ€. - Ragatantya, Vega Cyndra; Soesanto, Harry (Diponegoro Journal of Management, 2016)
This study examined the effect of product quality and brand image of behavioral intention. This research was conducted on consumers who consume products Antimo in Semarang.The population in this study are the people who use Antimo in Semarang, samples in this study were 96 respondent . Which in this study used a sampling technique by purposive sampling or sampling based on certain criteria , namely Semarang people who have been taking medicine Antimo more than 2 time , domiciled in the city of Semarang and is in the Region Bus Terminal and Bus Pool in Semarang.Based on hypothesis testing has proven that there is a positive influence between the brand image of the behavioral intention. there are positive influence between the quality of product to behavioral intention.